ANALISIS KINERJA INTERNAL, BALANCE SCORECARD DAN PENGEMBANGAN KEUANGAN MIKRO BERKELANJUTAN (STUDI PADA LEMBAGA PERKREDITAN DESA DI PROVINSI BALI) - Suartana, I Wayan; Ariyanto, Dodik (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
Starting in 1984 Baliâ€™s village micro financial institutions, which are called Lembaga Perkreditan Desa(LPD), were set up at the level of the customary village. These villages own, finance and govern the LPDs asan integral part of Balinese culture. The final say in every matter lies with the assembly of indigenousresidents (â€œkramaâ€), the ultimate authority in every village. This research is aimed to analyze the relationshipbetween LPD and contribution of LPD in order to reduce % percentace of population below the poverty line(%PBL). The independent variable Return on Asset (ROA) has contribution to reduce PBL. ROA is internalperformance of LPD. Additonal analysis is conducted by field experiment to explore improvement internalperformance of LPD with Balance Scorecard. Balance Scorecard is not only measurement tools but strategictools in order to reduce %PBL.Keywords:LPD, internal performance, balance scorecard and poverty